2022
DOI: 10.1167/iovs.63.13.13
|View full text |Cite
|
Sign up to set email alerts
|

Altered Structure and Function of Murine Sclera in Form-Deprivation Myopia

Abstract: Purpose The sclera is believed to biomechanically influence eye size, facilitating the excessive axial elongation that occurs during myopigenesis. Here, we test the hypothesis that the sclera will be remodeled and exhibit altered biomechanics in the mouse model of form-deprivation (FD) myopia, accompanied by altered retinoid concentrations, a potential signaling molecule involved in the process. Methods Male C57 Bl/6J mice were subjected to unilateral FD ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 81 publications
1
11
1
Order By: Relevance
“…We have also established that the myopic phenotype induced by atRA is accompanied by altered scleral biomechanics, with the sclera becoming more extensible and permeable, an effect consistent with that seen in visually mediated myopia in other species, 10 , 46 48 including our previous report in the mouse. 28 The overall impact of atRA on the eye appeared to be limited entirely to the posterior eye, except for a minor effect on anterior chamber depth that was also observed to occur in chickens. 24 We did not identify changes in scleral sGAGs or obvious signs of systemic or ocular toxicity.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We have also established that the myopic phenotype induced by atRA is accompanied by altered scleral biomechanics, with the sclera becoming more extensible and permeable, an effect consistent with that seen in visually mediated myopia in other species, 10 , 46 48 including our previous report in the mouse. 28 The overall impact of atRA on the eye appeared to be limited entirely to the posterior eye, except for a minor effect on anterior chamber depth that was also observed to occur in chickens. 24 We did not identify changes in scleral sGAGs or obvious signs of systemic or ocular toxicity.…”
Section: Discussionmentioning
confidence: 84%
“…Characterization of retinoids in the ocular tissues was performed as previously described. 28 In brief, the same tissues from left and right eyes of each animal were combined and weighed prior to homogenizing in 0.9% NaCl (normal saline). A two-step acid base extraction was performed, including internal standards (RA: 4,4-dimethyl-RA; retinol, total retinyl esters: retinyl acetate).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Citral is a competitive inhibitor of the key dehydrogenase required for RA generation. Studies have shown that the retinal RA content of myopia is significantly higher than that of non-myopia (Brown et al, 2022a;Brown et al, 2022b). Also, Wang et al found that the level of RA and the expression level of Zonula occludens-1 (ZO-1) and occludin in the retinal pigment epithelium (RPE) -choroid complex of lens induced myopia (LIM) guinea pigs were significantly increased, whereas the expression of RA and the proteins of ZO-1and occludin in LIM guinea pigs treated with RA antagonists were inhibited (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Retinoic acid (RA) is an acid derivative of vitamin A, which is the one-way oxidation product of photosensitive cells in the eye ( Brown et al, 2022a ; Brown et al, 2022b ), and RA has an important role in eye development. Citral is a competitive inhibitor of the key dehydrogenase required for RA generation.…”
Section: Introductionmentioning
confidence: 99%